2015
DOI: 10.1007/s10578-015-0564-9
|View full text |Cite
|
Sign up to set email alerts
|

Callous–Unemotional Traits as Markers for Conduct Problem Severity in Early Childhood: A Meta-analysis

Abstract: Extensive research has shown that callous-unemotional (CU) traits in middle-childhood and adolescence are markers for a particularly severe and chronic pattern of antisocial behavior (Frick et al. in Psychol Bull 140:1-57, 2014). Comparatively little, however, is known about the relationship between CU traits and antisocial behavior in early childhood. A meta-analysis of k = 10 studies comprising n = 5731 participants was conducted to examine the relationship between CU traits and conduct problem severity prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 53 publications
3
54
1
4
Order By: Relevance
“…Q‐statistics for tests of heterogeneity were used to examine effect size distributions. Statistically significant Q‐statistics indicate sources other than sampling error may result in differences in effect sizes (Longman, Hawes, & Kohlhoff, ). Random effects models were used to examine categorical moderators and meta‐regression analyses used to examine continuous moderator variables.…”
Section: Methodsmentioning
confidence: 99%
“…Q‐statistics for tests of heterogeneity were used to examine effect size distributions. Statistically significant Q‐statistics indicate sources other than sampling error may result in differences in effect sizes (Longman, Hawes, & Kohlhoff, ). Random effects models were used to examine categorical moderators and meta‐regression analyses used to examine continuous moderator variables.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, treatment research suggests that interventions implemented prior to school age, when behavior is potentially more malleable, are particularly efficacious (Reid, Webster-Stratton, & Baydar, 2004). Similar to CU traits in adolescence, CU behaviors measured as early as age 3 are uniquely related to lower guilt and empathy (Waller, Hyde, Grabell, Alves, & Olson, 2015) and predict later behavior problems (Longman, Hawes, & Kohlhoff, 2016; Waller, Hyde et al, 2015). CU behaviors in early childhood also predict CU traits in late childhood (Waller et al, 2016).…”
Section: Callous-unemotional (Cu) Behaviors In Early Childhoodmentioning
confidence: 99%
“…Recently, there has been a growing interest in studying CU traits in early childhood (Hyde et al, 2013;Kimonis et al, 2016), notably for its value in helping to identify children at risk for persistent and severe behavior problems and for prevention efforts (Frick et al, 2014). Recent studies have identified CU traits in children as young as 2 (Hyde et al, 2013), and meta-analytic findings indicate that there is a large, positive association between CU traits and conduct problems in early childhood (Longman, Hawes, & Kohlhoff, 2015). These findings suggest that CU traits in very young children are a meaningful risk factor for concurrent and future behavior problems.…”
mentioning
confidence: 99%